Effort angina pharmacotherapy in ambulatory practice - E. V. Gosteva (Кардиоваскулярная терапия и профилактика)
Aim. To assess the use of recommended standards for effort angina (EA) management and target achievement in EA pharmacotherapy among Voronezh general practitioners and district therapeutists.Material and methods. Therapy tactics and results were analyzed for 73 patients with coronary heart disease (CHD), Functional Class II-III EA, treated at 5 Voronezh polyclinics. At each polyclinic, one patient treated by a general practitioner, and one patient treated by a district therapeutist, were recruited.Results. In total, 95 % of Voronezh doctors used medications recommended by official treatment standards. In some patients, not achieving target heart rate levels due to lacking or inadequate heart rate-reducing therapy, ivabradine was administered.Conclusion. In ambulatory treatment of EA, ivabradine demonstrated a good heart rate-reducing effect and a significant reduction in angina attack rate.